USM MEDICAL SCIENCES PROGRAMME RECOGNISED BY IRANIAN GOVERNMENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 26 January 2017 – The Iranian Ministry of Health and Medical Education has officially accredited all the Medical Sciences programmes at Universiti Sains Malaysia (USM) as a result of its latest assessment of international universities.